An empirical method of determining employee competencies/KSAOs from task-based job analysis. - Goffin RD; Woycheshin DE (Military Psychology, 2006)
This article demonstrates a new, less subjective approach to determining employee competencies and KSAOs from task-based job analytic procedures. Incumbents rated tasks on their significance, which was a combination of importance and amount of time spent on the task, and in terms of the level of difficulty they personally experienced in completing the task, relative to other tasks. The relative difficulty ratings were interpreted as reverse-keyed ratings of incumbents' levels of proficiency on each task. Subjecting the task difficulty ratings of the most significant tasks to principal components analysis served to identify the competencies underlying task performance. The procedure was applied to the responses of 117 first-line public sector supervisors to a 307-item, task-based job analysis survey instrument and resulted in 6 meaningful competencies or KSAOs.